Knowledge and Attitude of Bangladeshi Physicians towards Organ Donation and Transplantation - Billah, Md Mostarshid; Farzana, Hafiza; Latif, Abdul; Mitra, Palash; Chowdhury, Tufayel Ahmed; Rahim, Muhammad Abdur; Hossain, Mohammad Jakir; Iqbal, Sarwar; Mansur, Md Abul; Faruq, Mohammad Omar; et al. (Bangladesh Critical Care Journal, 2016)
Background: Organ transplantation saves thousands of lives worldwide. There is discrepancy between organ demand and supply which demands cadaveric donation. Knowledge and attitudes of physicians towards organ donation and transplantation can increase the rate of organ and tissue donation by motivating general population. Methodology: This cross-sectional survey was done on 150 Bangladeshi physicians including specialist and post-graduate students on four teaching hospitals in Dhaka, Bangladesh over a period of six months. After taking informed consent, the participants were given a self-administered questionnaire which includes socio-demographic data, knowledge and attitude about organ donation and transplantation. Results: Male and female were almost equal (Total 102, Male 54, female 48) with mean age was 34.6±5.0 years and 54.9% were specialists and 45.1% were post graduate students. More than 32% respondents were from Medicine, followed by Nephrology (26.5%), Critical Care Medicine (CCM) (25.5%) and Urology (15.6%). Fifty-six (54.9%) physicians agreed with organ donation after death. The most important reason of agreement was to help others (78.4%) and disagreement was religious fear (54.3%). More than 40% respondents agreed and 59.8% completely disagreed with living kidney donation. The most common reason for agreement of living kidney donation was to donate to help family member (82.93%) and disagreement was probable damage to donors (52.46%). More than three-fourth (76.4%) respondents had knowledge about theoretical basis of transplantation, 50% know about cost and 43% about organ transplant Act, Bangladesh. Significant positive correlation was found between physicians attitudes towards organ and tissue donation after death and knowledge about theoretical basis of transplantation (p =0.02, r= 0.43) and cost of transplantation in Bangladesh (p= 0.02, r= 0.22) but no statistically significant correlation with knowledge about organ transplant Act, Bangladesh (p value= 0. 19, r= 0.13) whereas significant positive correlation between physicians knowledge about transplant Act (p= 0.008, r= 0.28), cost (p = 0.04, r= 0.23) and theoretical basis of transplantation (p= 0.04, r= 0.20) was found in living kidney donation. Conclusion: Physicians had a good attitude towards organ donation and transplantation although less than half of them had knowledge of transplantation rules and financial issues; therefore, additional awareness and education of physicians is needed in all areas of the organ transplant process in Bangladesh to make organ donation and transplantation successful. Bangladesh Crit Care J March 2016; 4 (1): 23-27